2004
DOI: 10.1023/b:ddas.0000034556.48527.6e
|View full text |Cite
|
Sign up to set email alerts
|

C-Reactive Protein as a Prognostic Variable That Reflects Uncontrolled Up-Regulation of the IL-1-IL-6 Network System in Colorectal Carcinoma

Abstract: Up-regulation of the IL-1-IL-6 network stimulates systemic expression of C-reactive protein (CRP). This cytokine network system plays a pivotal role in inducing angiogenic growth factors in intestinal mucosa. Serum CRP level and tissue concentrations of cytokines in colorectal cancer patients were determined and an in vitro model was employed to determine the time course of induction of IL-6 in Caco-2 cells. Increased serum CRP was associated with recurrent disease and shorter survival time. Intense surgical s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
67
0
1

Year Published

2005
2005
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 104 publications
(69 citation statements)
references
References 18 publications
1
67
0
1
Order By: Relevance
“…One of the most popular theories is that inflammatory cytokines, including interleukin (IL)‐1, IL‐6, and tumor necrosis factor (TNF), might promote tumor proliferation, survival, avoidance of apoptosis, progression of metastasis, and resistance to drug therapy. For example, Miki et al 56. have demonstrated that intense surgical stress and presence of an acute‐phase reactant were independently associated with the overexpression of IL‐6 in tumors.…”
Section: Resultsmentioning
confidence: 99%
“…One of the most popular theories is that inflammatory cytokines, including interleukin (IL)‐1, IL‐6, and tumor necrosis factor (TNF), might promote tumor proliferation, survival, avoidance of apoptosis, progression of metastasis, and resistance to drug therapy. For example, Miki et al 56. have demonstrated that intense surgical stress and presence of an acute‐phase reactant were independently associated with the overexpression of IL‐6 in tumors.…”
Section: Resultsmentioning
confidence: 99%
“…Angiogenesis plays an important role in tumour growth and is associated with a poor outcome in patients with GI tumours (Tanigawa et al, 1997;Fondevila et al, 2004). In addition, interleukin (IL) -1 and -6 network is upregulated (Vidal-Vanaclocha et al, 2000;Miki et al, 2004). Interleukin 1 is involved in the development of metastasis in animal studies and IL-6, apart from being a growth factor, promotes resistance to apoptosis (Vidal-Vanaclocha et al, 1994Chauhan et al, 1997;Frassanito et al, 2001;Jee et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…This might therefore suggest that interleukin-6 is produced by the tumour cells (Kinoshita et al, 1999;Belluco et al, 2000;Miki et al, 2004). If this were to prove to be the case, it would have important implications for the treatment of the systemic inflammatory response in patients with different tumours.…”
Section: Discussionmentioning
confidence: 99%